2020
DOI: 10.1038/s41598-020-64596-y
|View full text |Cite
|
Sign up to set email alerts
|

Pringle Maneuver in Extended Liver Resection: A propensity score analysis

Abstract: Despite the ongoing decades-long controversy, pringle maneuver (pM) is still frequently used by hepatobiliary surgeons during hepatectomy. The aim of this study was to investigate the effect of PM on intraoperative blood loss, morbidity, and posthepatectomy hemorrhage (PHH). A series of 209 consecutive patients underwent extended hepatectomy (eH) (≥5 segment resection). The association of pM with perioperative outcomes was evaluated using multivariate analysis with a propensity score method to control for conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…This finding is in similar line with our previously published report. Our results showed that PM is useful in patients who underwent extended liver resection, but this surgical maneuver may not be beneficial in minor hepatectomies 9 . It can be derived that PM is associated with encouraging early perioperative outcomes without worsening the long-term survival among well-selected patients.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…This finding is in similar line with our previously published report. Our results showed that PM is useful in patients who underwent extended liver resection, but this surgical maneuver may not be beneficial in minor hepatectomies 9 . It can be derived that PM is associated with encouraging early perioperative outcomes without worsening the long-term survival among well-selected patients.…”
Section: Discussionmentioning
confidence: 72%
“… Author (year) Country Study type Age Sample size Type of hepatectomy Duration of Pringle (min) Type of Pringle Diagnosis PM NPM PM NPM PM NPM Al-Saeedi (2020) 9 Germany Retrospective cohort 58.4 60.5 50 159 All patients underwent extended hepatectomy 19 Intermittent HCC and CRLM Lee (2019) 10 China Retrospective cohort 58 60.5 88 88 Minor: 51 (58.0%) Major: 37 (42.0%) Minor: 54 (61.4%) Major: 34 (38.6%) Mean (range) 45 (15–87) Intermittent HCC Famularo (2018) 4 Italy Retrospective cohort 65.1 67.6 176 265 Minor: 153 (87.4%) Major: 22 (12.6%) Minor: 228 (86.4%) Major: 36 (13.6%) Mean (range) 23 (14–30) Intermittent HCC Jiang (2017) 11 China Retrospective cohort NA NA ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total 29931 patients’ data who underwent liver resections for various etiologies were pooled from 41 studied included. [13-52]. 1257 patients died within 90 days post operatively.…”
Section: Resultsmentioning
confidence: 99%
“…Despite of the availability of modern devices controlling bleeding of parenchymal organs, temporarily clamping the hepatoduodenal ligament (Baron or Pringle maneuver) is still widely used in liver surgery for hepatic blood inflow control during major resections (open and laparoscopic/robotic surgery) to reduce bleeding and the need for perioperative blood transfusion [ 88 , 89 , 90 , 91 , 92 ]. Despite its obvious technical benefits during surgery, its use remains controversial due to potential negative effects on the clinical outcomes.…”
Section: Pathophysiology Of Hemorheological Alterations Related Tomentioning
confidence: 99%